Experimental analysis of railway track settlement in transition zones. (July 2018) - Wang, Haoyu; Markine, Valeri; Liu, Xiangming
Transition zones in railway tracks are the locations with considerable changes in the vertical support structures. Due to the differential stiffness and settlement in the open track and the engineering structure resulting in the dynamic amplification of the wheel forces, track settlement is usually observed in the approaching zones. The settlement in transition zones is detrimental to the track components and passenger comfort. This paper presents the results of the experimental analysis performed in three transition zones which were in various conditions. The dynamic displacements of rails due to passing trains were measured at multiple points (dynamic profile) in the approaching zones. The device employed is a contactless mobile device for measuring displacements, which is based on the digital image correlation technique. Because the operational parameters of the digital image correlation-based devices are important for measurement accuracy, prior to the in situ measurements, this device was tested in a laboratory to study the influence of the operational parameters, including the elevation/heading angles, the focal length of the cameras, and the measuring distance. After determining the optimal operational parameters for the railway field, multiple-point measurements were performed in the transition zones. The length of the approaching zone was studied first. Also, the dynamic profiles of the embankment–bridge and bridge–embankment transitions were analysed. Finally, by comparing the multiple-point displacements in the approaching zones in different conditions, it was found that the dynamic profile of the rail displacements has a good correlation with the track condition in the transition zone. The results are presented and discussed.